THE TRANSFORMATION OF THE SOCIAL BEING OF ETHNICITY AND THE FORMATION OF CIVIC CULTURE - DEMIRCHYAN, MOVSES (Bulletin of Yerevan University E: Philosophy, Psychology, 2019)
The article analyzes the process of transformation of ethnic culture, which evolutionarily goes to the formation of a nation. Taking into consideration the main theoretical approaches to understanding the phenomenon of a nation, it is indicated that the specialized literature pays little attention to the study of the transformations that take place at the basic level of the social existence of an ethnos. It is argued that the process of formation of the nation begins with changes in the social life of an ethnos, the main criterion of which is the organization of communal activity at a new, more complex level of social relations. They require to rethink the values, meanings, and goals of the coexistence of different groups of people, which implies the transformation of everyday and social life, that is, a change in the conditions of existence (being). In social philosophy, it is customary to comprehend the nation as a kind of an imaginary community of people, the basis of which is made up of common, real and mythical ideas about the origin, history, morality, and values. Many authors equate the nation and society. However, with the development of economic and political spheres of public life, national culture changes, so there arises a need for a rethinking of traditional concepts of morality, duty, responsibility, etc. The formation of civil society is associated precisely with the change in the living conditions of society or a nation, which, in turn, is a confirmation of the thesis that without a corresponding change in the social being of people neither a nation nor a civil society can be formed.